OPEN CELL METAL FOAM IN MODERN ENGINEERING APPLICATIONS: A REVIEW (Jurnal Teknologi (Sciences & Engineering), 2025)
Cell foam is a versatile material that has been employed in a wide range, of either structural or functional applications. The current review briefly explained an open cell foam (OCF) that can be made up from different materials i.e., ceramics, carbon, polymer and metal, depending on the applications being employed. Open cell metal foam (OCMF) appears to be in high demand and its applications have been extensively discussed in detail through this review. The OCMF possess unique properties like lightweight and porous structure that can be utilized in different fields such as thermal management, sound absorption, filtration and separation, energy absorption and impact protection, electromagnetic shielding, biomedical and medical device and other applications. OCMF seems to conquer most of the applications by considering characteristics of complex interior structure, high strength to weight ratio, large surface area and ability to absorb energy. The significant discovery from the literature is that the OCMF contributes into sustainability and has the potential to address limitations and challenges in emerging technologies and industries.